Outsourcing, Imperialism and Power: Master-Slave Dialectic in Rimini Protokoll's Call Cutta in a Box - Abdelfattah, Hany Ali Mahmoud (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2020)
يسلط البحث الضوء على التعهيد خارج الحدود كما ظهر في مسرحية الموقع المحدد كلكتا في صندوق لريمني بروتكول كمجاز عن جدلية السيد والعبد لهيجل. حيث توظف شركات التعهيد خارج الحدود، مثل شركة ديسكون المحدودة، عمالا هنودا في مراكز الاتصالات وتجبرهم، لاستمرار عملهم، على تخفيف اللكنة الهندية الثقيلة وتغيير الموقع الجغرافي لهم ليسهل لهم خداع العملاء الأوربي ين على خطوط التليفون الدولية وبالتالي يسهل إقناعهم أنهم أوروبيون مثلهم لتسويق بضائعهم. وهكذا غدت اللغة وتكنولوجيا الاتصالات سلاحين أساسيين في تجنيد العمال الهنود في مراكز الاتصالات لتقديم خدمة رخيصة الثمن للعملاء الأوربي ين. ويهدف البحث إلى الجابة عن الأسئلة: كيف أصبح التعهيد خارج الحدود حلقة من حلقات هيمنة الغرب على الشرق كيف فرض الاستعمار تعلم اللغة الإنجليزية على الهنود لخدمة العملاء الأوروبيين؟ كيف استحال العمال الهنود في سلم طبقي تكنولوجي يسبب الكثير من الضغوط عليهم ويسبب صعوبات في الاندماج مع مجتمعاتهم؟ كيف أن إتقان اللغة والتكنولوجيا يسب بـــــ"إدراكا" و"استقلالية" للهنود ضد أسيادهم الأوروبيين كما جاء في نظرية هيجل؟ ما هي آلية استخدام مسرح الموقع المحدد في كالكتا؟
This paper investigates how offshore outsourcing, as represented in Rimini Protokoll’s site-specific play Call Cutta in a Box, is a metaphor of the Hegelian Master-slave dialectic. Offshore outsourcing corporations, like Descon Limited, employ Indian call center operators and force them to have intense training to neutralize their thick Indian accents and mask their GPS location to defraud European customers at the other end of the line. Language and Information Technology have been used by these global corporations to enslave Indian workers and to provide a service of high quality to European customers. The paper seeks to find answers to the questions: How is offshore outsourcing an important phase in the trajectory of the imperialistic hegemony of the West over the East? How did colonialism impose the English language on Indians to turn them into mere servants to their purposes? How does the hierarchical power structure cause immense stress on Indian call center operators? How do the Indians payback by mastering Information Technology, thus gaining ‘recognition’ and ‘independence’ from the masters? What is the function behind using a call center in Kolkata as a site-specific theatre?
Keywords: مسرحية كلكتا في صندوق -- بروتكول، ريمني -- النقد الأدبي -- جدلية السيد والعبد